Utopia’s Moorish Inspiration: Thomas More’s Reading of Ibn Ṭufayl - Regnier, Daniel (Renaissance and Reformation / Renaissance et Réforme, 2018)
A promising but neglected precedent for Thomas More’s Utopia is to be found in Ibn Ṭufayl’s Ibn Ḥayy Yaqẓān. This twelfth-century Andalusian philosophical novel describing the self-education and enlightenment of a feral child on an island, while certainly a precedent for the European Bildungsroman, also arguably qualifies as a utopian text. It is possible that More had access to Pico de la Mirandola’s Latin translation of Ibn Ḥayy Yaqẓān. This study consists of a review of historical and philological evidence that More may have read Ibn Ḥayy Yaqẓān and a comparative reading of More’s and Ṭufayl’s two famous works. I argue that there are good reasons to see in Ibn Ḥayy Yaqẓān a source for More’s Utopia and that in certain respects we can read More’s Utopia as a response to Ṭufayl’s novel.